Potensi Antioksidan Buah Pare (Momordica Charanti L) Terhadap Dislipidemia - Andestya Nanda Pratama (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Dyslipidemia is a body’s lipid fraction abnormalities caused by the poor food intake or bad dietary habit o consuming high lipid and low fiber. Coronary Heart Disease (CHD) as the most ailment that kills people these last few years is mostly caused by dyslipidemia. Medicine intakes as the main treatment of dyslipidemia caused a lot of side effects. Bitter melon fruit (Momordica Charanti L) which contains so many high antioxidants can be the alternative option to minimize these side effects. Flavonoid, saponin, vitamin C, and vitamin D, the natural compound of antioxidants in bitter melon fruit (Momordica Charanti L) proved by most national and international articles, have the mechanism of affecting the lipid fraction. These antioxidants intensify the HDL (High-density lipoprotein) and reduce the LDL (Low-density lipoprotein), triglycerides, and total cholesterol level that normalize the body’s lipid fraction abnormalities.